Relationship between Job Equity and Performance of Employee: A Literature Review - Inuwa, Mohammed (International Journal of Business and Management Future, 2017)
Job equity plays a great role in enhancing employee’s performance in the work place. Previous studies however, concentrate on other aspect that motivate an employee to perform while discussing little on how of job equity and perceived fairness as well as how its repercussion on performance of an employee. This study therefore, adopts job equity as an independent variable and employee performance as a dependent variable with the aim analysing how perceived job equity enhances employee performance. The paper reviews past studies and literatures by various researchers and come to the conclusion that job equity plays an important role in boosting employee morale and enhancing performance. Consequently, the paper recommends that managers, employers and organisation as a whole should ensure that equity and fairness is always at play in all levels of decision making, thereby making the employee safe and secured, which result in higher performance and productivity. Moreover, paper will serve as a guide towards ensuring organisational justice and it will also contribute to the field organisational behaviour and management. It also adds more details to Adams equity theory and its applicability in today’s work place.